An Cailín Ciúin : choix esthétiques et politiques du cinéma en gaélique - Valentine Lerouge (Lengas)
This article uses An Cailín Ciúin, Colm Bairéad’s 2022 debut film, as a case study to examine the the representations of Ireland as well as the vision of Gaelic it conveys, in the context of rising television and film production in the Irish language. It showcases how recent legislative policies have created a favorable context for the emergence of a strong Irish-language cinema. By analyzing the film through the lens of the short story it adapts, Claire Keegan’s Foster, the article aims at uncovering the echoes between adaptation and translation, as well as how the use of Gaelic contributes to the overall signification of the short story. The article further sheds light on Bairéad’s aestheticised representation of rurality in Ireland, which presents viewers with a conventional use of Irish tropes.